2019
DOI: 10.22178/pos.45-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Modelling to Study the Electrochemical Behaviour of PdO, TiO2 and Perovskite-Type LaFeO3 Modified Carbon Paste Electrodes

Abstract: Transition metals are highly sought after in electrode construction due to their eventual electrocatalytic effects. In this context, this work presents the study of several metal oxide modified electrodes focusing in the evaluation of their electrochemical features through voltammetry and Electrochemical Impedance Spectroscopy (EIS). Moreover, a predictive statistical model was also developed using LASSO regression. Henceforth, glassy carbon electrode (GCE) and carbon paste electrode (CPE) were used to establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Voltammetric assays were performed in buffers purged with nitrogen gas in order to avoid oxygen interference. The electrochemical area of the carbon paste electrode was 7.77 mm 2 , as estimated in a previous work of our group [31]. The CPE was cleaned and the surface was renewed after each assay.…”
Section: Methodsmentioning
confidence: 99%
“…Voltammetric assays were performed in buffers purged with nitrogen gas in order to avoid oxygen interference. The electrochemical area of the carbon paste electrode was 7.77 mm 2 , as estimated in a previous work of our group [31]. The CPE was cleaned and the surface was renewed after each assay.…”
Section: Methodsmentioning
confidence: 99%
“…Literature reports that electrochemistry is a valuable approach to investigate redox processes in organic compounds, being voltammetry, the most common technique used to characterize electron transfer phenomena on working electrode surfaces [20,21]. In this sense, we employed cyclic voltammetry to gather information of all redox processes underwent by TRA in the selected electric potential interval.…”
Section: Discussionmentioning
confidence: 99%
“…The anodic and cathodic processes seen at Figure 2 indicate that electroactive moieties in TRA molecule underwent oxidation and reduction, respectively. Considering that the electric current corresponds to the kinetic parameter of a redox reaction seen in a voltammogram, while the electric potential corresponds to the thermodynamic parameter [20], it can be suggested that more energy is needed to promote the oxidation indicated by peak 2a than to promote the oxidation seen at 1a. In addition, peak 2a was clearly higher, therefore suggesting higher kinetics (although capacitive influences cannot be ruled out).…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, the mixture of MTX and DNA from each lineage was submitted to several CV under crescent υ, in order to obtain the plots of the faradaic currents versus the square root of the voltametric scan rate, as stated by Randles-Sevcik equation (1). This mathematical treatment was used given that it allows us to draw comparisons regarding diffusional aspects of the electrochemical reaction [15].…”
Section: Electrochemical Assaysmentioning
confidence: 99%